Antibiotic-resistant Salmonella and Escherichia coli isolates with integrons and extended-spectrum beta-lactamases in surface water and sympatric black-headed gulls - Dolejská, M; Bierosová, B; Kohoutová, L; Literák, I; Cízek, A (Journal of applied microbiology, 2009)
AIM: To examine surface water from a pond in the northeastern part of the Czech Republic and young black-headed gulls (Larus ridibundus) nesting on the same pond for the presence of antibiotic-resistant Salmonella and Escherichia coli. METHODS AND RESULTS: A total of 16% (n = 87) of water and 24% (n = 216) of gull samples yielded Salmonella. Salmonella Enteritidis PT8 and PT4 were the most prevalent. Antibiotic resistance was found in 12% (n = 14) of water and 28% (n = 51) of gull salmonellae. Escherichia coli were found in 83 (95%) and 213 (99%) of pond water and gull samples, respectively. Totals of 18% (n = 83) of water and 28% (n = 213) of gull E. coli isolates were resistant to antimicrobial agents tested. Class 1 integrons were found in 21% (n = 14) of water and 15% (n = 60) of gull antibiotic-resistant E. coli isolates. Class 2 integrons and extended-spectrum beta-lactamase-producing E. coli isolates (with bla(CTX-M-1), bla(CTX-M-15)-like, bla(SHV-2) and bla(SHV-12)) were found in 13% (eight positive, n = 60 gull-resistant E. coli isolates) and 3% (seven positive, n = 216 gull E. coli isolates) of gull isolates, respectively. Antibiotic-resistant E. coli isolates with identical pulsed field gel electrophoresis (PFGE) patterns were found in either gulls or water, but not both. Salmonellae of the same serotype and PFGE profile were found in both gulls and water. CONCLUSION: A high prevalence of antibiotic-resistant salmonellae and E. coli were found in both pond water and in sympatric black-headed gulls. SIGNIFICANCE AND IMPACT OF THE STUDY: Intensive contamination of pond surface water by antibiotic-resistant E. coli and salmonellae was documented. Black-headed gulls were identified as important reservoirs of antibiotic-resistant salmonellae and E. coli, including extended-spectrum beta-lactamase-producing isolates.
Keywords: Microbial Sensitivity Tests; Disease Reservoirs; DNA bakterií; antibiotická rezistence; Integrons; pulzní gelová elektroforéza; zdroje nemoci; mikrobiální testy citlivosti; Escherichia coli; Charadriiformes; Electrophoresis, Gel, Pulsed-Field; zvířata; beta-laktamasy; DNA, Bacterial; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; beta-Lactamases; Drug Resistance, Microbial; Animals; Česká republika; integrony; Salmonella